2020
DOI: 10.1111/1365-2656.13333
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits explain trophic allometries of cephalopods

Abstract: 1. Individual body size strongly influences the trophic role of marine organisms and the structure and function of marine ecosystems. Quantifying trophic positionindividual body size relationships (trophic allometries) underpins the development of size-structured ecosystem models to predict abundance and the transfer of energy through ecosystems. Trophic allometries are well studied for fishes but remain relatively unexplored for cephalopods. 2. Cephalopods are important components of coastal, oceanic and deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 93 publications
(123 reference statements)
3
15
0
Order By: Relevance
“…High activity cephalopods identified by Murphy et al . (2020) had thick muscular mantles, larger firmer fins, and a fin length that is 50% or greater than the mantle length. The huge fins of I. cordiformis tend to dominate the organism and are well over 50% of the mantle length, but the mantle is not thick and muscular, which limits the application of categories suggested by Murphy et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High activity cephalopods identified by Murphy et al . (2020) had thick muscular mantles, larger firmer fins, and a fin length that is 50% or greater than the mantle length. The huge fins of I. cordiformis tend to dominate the organism and are well over 50% of the mantle length, but the mantle is not thick and muscular, which limits the application of categories suggested by Murphy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Murphy et al . (2020) used morphological traits to classify cephalopods into three functional groups based on low, medium and high activity levels as well as feeding mode (from passive feeders to active hunters). These factors along with body size were used to infer trophic position.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these findings, recent research exploring trophic allometries in cephalopods have also suggested that there are some species or Families (i.e., Cranchiidae) that do not exhibit ontogenetic trophic position shifts across different size classes, differing from the general description of cephalopod as voracious predators. These low activity level cephalopods were characterized by having low trophic positions, feeding largely upon herbivorous zooplankton and do not shifting to higher levels of piscivory until larger sizes (see Murphy et al, 2020).…”
Section: Trophic Ecology Of D Gahi In Northern-central Chilementioning
confidence: 99%
“…Despite important roles as major foraging predators with prey preferences and avoidances but no individual specialization (Marsteller, 2018) and as prey in benthic marine communities, and the possible impact of fishing on ecosystem functioning (Sauer et al, 2019), systematic studies on the GPO trophic niche (trophic pathways and positions) in coastal marine food webs are still lacking compared with squids (Hobson and Cherel, 2006;Merten et al, 2017;Murphy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, their diet compositions may seldom capture topological descriptions of food webs to characterize their trophic niche (Kang et al, 2020). Alternatively, carbon and nitrogen stable isotope analyses (referred to here as δ 13 C and δ 15 N values, respectively) have been applied successfully to the identification of diets, feeding habits, and trophic ecology of cephalopods (Cherel et al, 2009;Merten et al, 2017;Murphy et al, 2020). The dietary resources of a species within a marine food web can be resolved by the δ 13 C values of its tissues, as the latter contains information on the source (benthic or pelagic) of prey items (Kang et al, 2008;Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%